Synonymy of Quadraseta brennani Goff & Whitaker, 1984 with Quadraseta antillarum (Brennan, 1967) (Trombidiformes: Trombiculidae) - Huang-Bastos, Matheus (2022)
Chiggers are ectoparasites of vertebrates and can cause trombiculiasis or transmit pathogens to their hosts. I n the Neotropical region, the genus Quadraseta Brennan includes 16 valid species. Quadraseta antillarum (Brennan) and Quadraseta brennani (Goff & Whitaker), are morphologically identical and we propose th e synonymy of Q. brennani with Q. antillarum, based on examination of both type series. The little big-eared bat, Micronycteris megalotis Gray from Venezuela is recorded as a new host.